The impact of improved surgical safety checklist participation on OR efficiencies: A pretest-post test analysis - Brigid Gillespie; Emma Harbeck; Joanne Lavin; Therese Gardiner; Teresa Withers; Andrea Marshall (Journal of Perioperative Nursing)
Objective: To describe changes in day of surgery (DOS) cancellations and procedural delays following introduction of a practice improvement intervention to improve team members’ participation in the surgical safety checklist (SSC).